A Long Run ARDL Investigation of Manufacturing Adjustment to the Services Economy in Nigeria - Olamade, Olumuyiwa (Asian Development Policy Review, 2021)
The long-run equilibrating relationship between the value-added growth of services and manufacturing is investigated in this research. The study is based on the well-established empirical link between manufacturing and service activities, and in particular, manufacturing's servicification. The selected variables' annualized time series were obtained from the World Development Indicators. The paper used the autoregressive distributed lag framework to regress manufacturing value-added growth against service value-added growth while accounting for economic growth, factor input growth, and trade effects. The findings revealed that in Nigeria, a strong performing services sector has a large negative impact on manufacturing performance, whereas capital accumulation and income growth have positive effects. The supply constraint of business services that the manufacturing sector requires is at the root of this finding. The paper advocates for policy frameworks that support the efficient supply of business services as both a manufacturing input and a productivity enhancer for the entire economy.